2010
DOI: 10.1002/clc.20663
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing‐induced Atrial Tachyarrhythmia Triggered by Salbutamol: Case Report and Review of the Literature

Abstract: Salbutamol is presented here as a possible trigger for SIAT. Although it is difficult to define causality in a case report, it is logical to think that a beta-agonist like salbutamol (known to induce tachycardia) may be the trigger of adrenergic reflexes originating in the esophagus while swallowing and that a beta-blocker such as atenolol (that blocks the adrenergic activity) may relieve it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
(29 reference statements)
0
16
0
1
Order By: Relevance
“…According to their results, swallowing decreases heartbeat period abnormally and causes syncope at people who have some oesophageal or cardiac diseases. According to Tandeter et al (2010), possible causes of this tachycardia include vasovagal reflexes, adrenergic reflexes of the oesophagus and mechanical stimulation of the left atrium by swallowing. For healthy people, it was reported that voluntary swallowing changes some of the HRV parameters (SDNN, LF, HF power) significantly (Yazgi & Yildiz, 2009) and effortful swallowing increases LF power and LF/HF ratio (Gomes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to their results, swallowing decreases heartbeat period abnormally and causes syncope at people who have some oesophageal or cardiac diseases. According to Tandeter et al (2010), possible causes of this tachycardia include vasovagal reflexes, adrenergic reflexes of the oesophagus and mechanical stimulation of the left atrium by swallowing. For healthy people, it was reported that voluntary swallowing changes some of the HRV parameters (SDNN, LF, HF power) significantly (Yazgi & Yildiz, 2009) and effortful swallowing increases LF power and LF/HF ratio (Gomes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the concurrent administration of these PDE inhibitors and β 2 -AR agonists should be closely watched, particularly in patients with significant cardiac disease such as ischemic or congestive heart disease, in whom the risk of acute cardiac death is increased in response to bronchodilators (Suissa et al, 1996). Conversely, β 1 -AR antagonists may reduce this risk of pro-arrhythmia and recent clinical evidence indicates that this may be the case (Tandeter et al, 2010). Although, the administration of β-AR blockers to patients with reactive airway disease is considered to be contraindicated because they can induce bronchoconstriction after acute dosing, recent evidence suggests that they may not be so harmful in these patients.…”
Section: Salbutamol (Log M)mentioning
confidence: 95%
“…B: Cardiac magnetic resonance imaging illustrating large HH (red arrows) in close proximity to the LA. А B пищевод, заканчивая вздутием живота и дефекацией [26,27,28]. Описаны случаи спонтанного восстановления синусового ритма после проведения операции фундопликации по Ниссену у больных с пароксизмальной формой ФП при отсутствии иной кардиальной патологии [29].…”
Section: Figureunclassified